Genome-Wide Identification and Evolution Analysis of Trehalose-6-Phosphate Synthase Gene Family in Nelumbo nucifera - Jin, Qijiang; Hu, Xin; Li, Xin; Wang, Bei; Wang, Yanjie; Jiang, Hongwei; Mattson, Neil; Xu, Yingchun (Frontiers in Plant Science, 2016)
Trehalose-6-phosphate synthase (TPS) plays a key role in plant carbohydrate metabolism and the perception of carbohydrate availability. In the present work, the publicly available Nelumbo nucifera (lotus) genome sequence database was analyzed which led to identification of nine lotus TPS genes (NnTPS). It was found that at least two introns are included in the coding sequences of NnTPS genes. When the motif compositions were analyzed we found that NnTPS generally shared the similar motifs, implying that they have similar functions. The dN/dS ratios were always less than 1 for different domains and regions outside domains, suggesting purifying selection on the lotus TPS gene family. The regions outside TPS domain evolved relatively faster than NnTPS domains. A phylogenetic tree was constructed using all predicted coding sequences of lotus TPS genes, together with those from Arabidopsis, poplar, soybean and rice. The result indicated that those TPS genes could be clearly divided into two main subfamilies (I-II), where each subfamily could be further divided into 2 (I) and 5 (II) subgroups. Analyses of divergence and adaptive evolution show that purifying selection may have been the main force driving evolution of plant TPS genes. Some of the critical sites that contributed to divergence may have been under positive selection. Transcriptome data analysis revealed that most NnTPS genes were predominantly expressed in sink tissues. Expression pattern of NnTPS genes under copper and submergence stress indicated that NNU_014679 and NNU_022788 might play important roles in lotus energy metabolism and participate in stress response. Our results can facilitate further functional studies of TPS genes in lotus.